Role of Exercise Intensity on Th1/Th2 Immune Modulations During the COVID-19 Pandemic - Supriya, Rashmi; Gao, Yang; Gu, Yaodong; Baker, Julien S. (Frontiers in Immunology, 2021)
The COVID-19 pandemic has led to several pioneering scientific discoveries resulting in no effective solutions with the exception of vaccination. Moderate exercise is a significant non-pharmacological strategy, to reduce the infection-related burden of COVID-19, especially in patients who are obese, elderly, and with additional comorbidities. The imbalance of T helper type 1 (Th1) or T helper type 2 (Th2) cells has been well documented among the populations who have suffered as a result of the COVID-19 pandemic, and who are at maximum risk of infection and mortality. Moderate and low intensity exercise can benefit persons at risk from the disease and survivors by favorable modulation in Th1/Th2 ratios. Moreover, in COVID-19 patients, mild to moderate intensity aerobic exercise also increases immune system function but high intensity aerobic exercise may have adverse effects on their immune responses. In addition, sustained hypoxia in COVID-19 patients has been reported to cause organ failure and cell death. Hypoxic conditions have also been highlighted to be triggered in COVID-19-susceptible individuals and COVID-19 survivors. This suggests that hypoxia inducible factor (HIF 1α) might be an important focus for researchers investigating effective strategies to minimize the effects of the pandemic. Intermittent hypoxic preconditioning (IHP) is a method of exposing subjects to short bouts of moderate hypoxia interspersed with brief periods of normal oxygen concentrations (recovery). This methodology inhibits the production of pro-inflammatory factors, activates HIF-1α to activate target genes, and subsequently leads to a higher production of red blood cells and hemoglobin. This increases angiogenesis and increases oxygen transport capacity. These factors can help alleviate virus induced cardiopulmonary hemodynamic disorders and endothelial dysfunction. Therefore, during the COVID-19 pandemic we propose that populations should engage in low to moderate exercise designed individually and specific, that utilizes IHP including pranayama (yoga), swimming and high-altitude hiking exercise. This would be beneficial in affecting HIF-1α in order to combat the disease and its severity. Therefore, the promotion of certain exercises should be considered by all sections of the population. However, exercise recommendations and prescription for COVID-19 patients should be structured to match individual levels of capability and adaptability.